Pengaruh Model Jigsaw Terhadap Hasil Belajar Menulis Cerpen Kelas IX Di MTsS Al-Badar Kediri - Andriana, Nia; Hardinanto, Eko (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
This study examines the effectiveness of the application of the Jigsaw learning model on the short story writing skills of grade IX students at MTsS Al-Badar Kediri. Jigsaw is a cooperative learning model that encourages active participation, group cooperation, and a deeper understanding of the material. This study used an experimental method with two groups, namely the experimental group that applied the Jigsaw model and the control group that used conventional methods. The sample was selected purposively from grades IX-A and IX-B. Data collection was carried out through pretests, posttests, observations, and interviews. The results showed a significant increase in short story writing skills, especially in story structure, language use, creativity, and plot development. The t-test analysis confirmed that the Jigsaw model contributed positively to student learning outcomes. Based on these findings, it is recommended to strengthen the application of Jigsaw by emphasizing cooperation between students and the use of technology in learning.